دراسة توزع المركبات الهيدروكربونية متعددة الحلقات العطرية (PAHs) في رسوبيات ومياه شاطئ مدينة طرطوس باستخدام تقانتي الاستخلاص والكروموتوغرافيا الغازية - ناصر, محمد; حويجة, عماد (Latakia University Journal -Basic Sciences Series, 2018)
جمعت عينات مياه شاطئية من ثلاثة مواقع على شاطئ مدينة طرطوس ، بالإضافة إلى ذلك تم جمع عينات رسوبية شاطئية من سبعة مواقع على شاطئ مدينة طرطوس خلال الفترة الزمنية الممتدة من 1/6/2001 ولغاية 15/6/2002 وجرى استخلاصها ودراستها كمياً ونوعياً باستخدام تقانة الكروموتوغرافيا الغازية GC-FID من أجل تحديد الفحوم الهيدروجينية متعددة النوى العطرية (PAHs).تراوحت تراكيز الـ (PAHs) في الرسوبيات المدروسة مابينnd- 264.9 ng/g (dry wt. ). سجلـت أعلى التراكيز في المحـطة st3 ، وأخفض التراكيز في المحطة St6 ، أما المحطات st4 و st5و st1 فكانت تراكيز الـ (PAHs) فيها دون عتبة الكشف. سجلـت تراكيز الـ (PAHs) في المياه المدروسة في المجال nd-139.3 ng/l . كانت أعلى التراكيز في المحـطة الواقعة داخل مرفأ أرواد ومرفأ الصيد البحري. وأخفضها في المحطة المقابلة لمصب نهر الحصين. Coastal waters from three sites and samples of tidal sediments from seven sites of Tartous city coast were collected during the period (1/6/2001-15/6/2002). The samples were extracted to determine their content of Polycyclic Aromatic Hydrocarbons (PAHs) qualitatively and quantitively by using GC-FID technique. The concentration of (PAHs) ranged between nd and 264.9 ng/g (dry wt.). The highest concentration was reported in st3, while the lowest concentration was reported in St6. The values of (PAHs) reported in st4, st5, and st1 were lower than of the detected threshold. The concentration of (PAHs) ranged between nd and 139.3 ng/l. The highest concentration was reported in Aroad port and fishing port, while the lowest concentration was reported in the station opposite the discharging point Al-Hesein river.